Kajian Nilai Pada Tradisi Perang Pisang Di Desa Tenganan Dauh Tukad, Kecamatan Manggis, Kabupaten Karangasem - Ida bagus Putu eka Suadnyana (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2021)
ABSTRACTTri Hita Karana is an effort to create three forms of living relationships as a unit that can form a harmonious living climate in society. Three forms of relationships that build a harmonious living climate are created by a balanced attitude of life between being devoted to Ida Sang Hyang Widhi, serving fellow humans and maintaining the welfare of the natural environment. Tradition is a habit passed on by ancestors and carried out from generation to generation in a society. The banana war tradition is a tradition in Tenganan Dauh Tukad Village which is held once a year, coinciding with the third aci in the local village, which is around April according to wariga calculations in Tenganan Dauh Tukad Village. The banana war tradition is carried out as a physical and mental test in order to select prospective leaders, in order to obtain a strong leader. In addition, the banana war was also carried out as a form of conveying gratitude for the people of Tenganan Dauh Tukad Village to Ida Sang Hyang Widhi for the harvest that had been obtained. This research is in the form of a qualitative design with a qualitative approach. Data collected using interview techniques, observation techniques and document study. After the data was collected, the data were analyzed by means of interpretive descriptive data analysis. The banana war tradition is carried out in the context of selecting leaders in Tenganan Dauh Tukad Village which is a physical and mental test to get a strong leader, the process of implementing the banana war is hanging a goat, holding I, nycah ulu-ulu, ngerampag or ngalang I, ngerampag or ngalang II. and the implementation of the banana war, the values contained in the banana war are tattwa values, ethical values, aesthetic values, mutual cooperation and togetherness values as well as Hindu leadership values. Keywords: Value Study, Tradition, Banana War